Rotating shaft, air cycle machine and manufacturing method of rotating shaft
By providing a copper film as an intermediate transition layer on the surface of the rotary shaft, the problem of high residual stress after cooling of the H-DLC film is solved, the risk of brittle fracture is reduced, and the wear resistance and stability of the rotary shaft are improved.
Patent Information
- Application Number
- CN202411340051.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The hydrogenated diamond-like (H-DLC) film on the surface of the rotating shaft generates large residual stress during cooling, resulting in brittle fracture and vibration problems.
A copper film is provided as an intermediate transition layer on the surface of the rotary shaft to alleviate the residual stress caused by mismatch in the thermal expansion coefficient, and a low hardness of the copper film and good film-based bonding force are used to reduce the residual stress of the H-DLC film.
It effectively reduces the residual stress of the H-DLC film, enhances the film-based binding force, avoids brittle fracture, and improves the wear resistance and stability of the rotating shaft.
Smart Images

Figure CN119266928A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rotating shafts, and in particular relates to a rotating shaft, an air cycle machine and a method for manufacturing the rotating shaft. Background Art
[0002] The transmission shaft of the turbine of the air cycle machine is supported by an air dynamic bearing, so the transmission shaft and the top foil of the bearing will have dry friction during the start and stop stages. Dry friction can easily lead to the removal of material on the shaft surface, which in turn leads to large vibrations during the rotation of the transmission shaft. To solve this problem, a hydrogenated diamond-like carbon (H-DLC) film is used on the surface of the transmission shaft to modify its surface, and the shaft substrate is alloy steel. The temperature during the manufacturing process of the H-DLC film is relatively high (about 500°C). When the manufacturing is completed and the temperature is reduced to room temperature (about 25°C), due to the huge difference in thermal expansion coefficient between the H-DLC film and the film substrate during preparation, the H-DLC film will produce a large residual stress after it is reduced from high temperature to low temperature. This stress will cause the H-DLC film to easily fracture brittlely when it is impacted by external forces.
[0003] How to reduce the residual stress of the H-DLC film on the shaft surface is a technical problem that urgently needs to be solved. Summary of the invention
[0004] Therefore, the present invention provides a rotating shaft, an air cycle machine and a method for manufacturing the rotating shaft, which can solve the technical problem of large residual stress of the H-DLC film on the surface of the rotating shaft in the prior art.
[0005] In a first aspect, the present invention provides a rotating shaft, comprising a base shaft, the surface of the base shaft being covered with a hard film, the hardness of the hard film being greater than the hardness of the base shaft, and only a copper film being arranged between the base shaft and the hard film, the hardness of the copper film being less than the hardness of the base shaft.
[0006] In some embodiments, the hard film is hydrogenated diamond-like carbon.
[0007] In some embodiments, the copper film has a thickness of H1, and thus 0.003 mm ≤ H1 ≤ 0.004 mm.
[0008] In some embodiments, the hard film has a thickness of H2, and 0.003 mm ≤ H2 ≤ 0.004 mm.
[0009] In a second aspect, the present invention provides an air cycle machine, comprising an air dynamic pressure bearing and the rotating shaft, wherein a top foil of the air dynamic pressure bearing is opposite to an outer peripheral surface of the rotating shaft.
[0010] The third invention, the present invention also provides a method for manufacturing a rotating shaft, the manufacturing method is used for manufacturing the rotating shaft;
[0011] The manufacturing method comprises: step 1, processing the surface of the base shaft; step 2, manufacturing a copper film on the surface of the base shaft; and step 3, manufacturing a hard film on the surface of the copper film.
[0012] In some embodiments, the base shaft is an iron base shaft, and the step 1 includes, S11: grinding the surface roughness of the base shaft to no greater than Ra0.08;
[0013] S12: The surface of the base shaft is cleaned for 9 to 11 minutes, then ultrasonically cleaned for 14 to 16 minutes, and finally blown dry.
[0014] In some embodiments, step 2 includes:
[0015] S21: Place the copper target on the top of the magnetron sputtering chamber and evacuate the magnetron sputtering chamber to a pressure no greater than 5×10 - 5 Pa;
[0016] S22: applying a voltage of -348 V to -352 V to the copper target, while sputtering the copper target with argon gas at a flow rate of not less than 30 sccm, while maintaining the pressure in the magnetron sputtering chamber at 0.4 Pa to 0.5 Pa, and the process lasts for 2.5 to 3.5 minutes;
[0017] S23: Stop applying voltage to the copper target, place the base shaft 1 on the top of the magnetron sputtering chamber, and evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, and argon gas continues to sputter the copper target at a flow rate of not less than 30 sccm, while the pressure in the magnetron sputtering chamber is maintained at not higher than 0.5 Pa, and the temperature in the sputtering chamber is between 50°C and 80°C. The process lasts for 45 to 55 minutes.
[0018] In some embodiments, S12 includes: cleaning the surface of the base shaft with acetone, ultrasonically cleaning with anhydrous ethanol, and drying with nitrogen.
[0019] In some embodiments, the hard film is an H-DLC film, and the step three includes:
[0020] S31: Replace the copper target with a graphite target with a purity of not less than 99.9% and place it on the top of the magnetron sputtering chamber. Evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, temperature is in the range of 480℃~520℃;
[0021] S32: applying a substrate bias voltage of -348V to -352V to the graphite target, and simultaneously sputtering the graphite target with a mixed gas of argon and methane at a flow rate of not less than 150sccm, wherein the ratio of argon to methane is between 2.2 and 2.5, and the process lasts for 20 to 25 hours.
[0022] In some embodiments, the step three further comprises:
[0023] S33: Cooling the temperature in the sputtering chamber to between 25°C and 30°C at a rate of (0.3-0.4)°C / min.
[0024] A copper film is set between the base shaft and the hard film. Since the hardness of copper is lower than that of the base shaft and the hard film, the copper film can alleviate the high residual internal stress of the hard film caused by the mismatch of thermal expansion coefficients when the high temperature environment of the preparation is cooled to room temperature. The shaft using the copper film as the intermediate transition layer has good film-base bonding and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0026] Figure 1 is a schematic diagram of the relationship between the rotating shaft and the air dynamic pressure bearing of an embodiment of the present invention;
[0027] Figure 2 is an axial schematic diagram of a rotating shaft according to an embodiment of the present invention;
[0028] Figure 3 is a radial cross-sectional schematic diagram of a rotating shaft according to an embodiment of the present invention;
[0029] Figure 4 is a schematic diagram of the axial stress distribution of H-DLC when cooled to 20° C. when a copper film and H-DLC are provided in an embodiment of the present invention;
[0030] Figure 5 The embodiment of the present invention is provided with a copper film and H-DLC, and a schematic diagram of the axial stress distribution of the bonding surface of the H-DLC and the copper film when cooled to 20°C;
[0031] Figure 6 The embodiment of the present invention is provided with a copper film and H-DLC, and when cooled to 20° C., a schematic diagram of the axial residual stress at the interface between the H-DLC and the copper film;
[0032] Figure 7 It is a schematic diagram of the axial stress distribution of H-DLC when cooled to 20°C when the prior art is always provided with only H-DLC;
[0033] Figure 8It is a schematic diagram of the axial stress distribution on the interface between H-DLC and the base shaft when the base shaft is cooled to 20° C. when only H-DLC is provided in the prior art;
[0034] Fig. 9 It is a schematic diagram of the axial residual stress of the interface between H-DLC and the base shaft when the base shaft is cooled to 20° C. when only H-DLC is provided in the prior art;
[0035] The accompanying drawings are marked as follows:
[0036] 1. Base shaft; 2. Hard film; 3. Copper film; 4. Air dynamic pressure bearing. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the devices or elements referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention. The directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.
[0039] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.
[0040] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. If not otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0041] The residual stress of the H-DLC film on the surface of the shaft is generated by cooling the H-DLC film to room temperature after the H-DLC film is prepared at the ambient temperature during magnetron sputtering. Specifically, when preparing the H-DLC film, the base shaft is subjected to a high temperature of about 500°C, and the H-DLC film is formed at this temperature. At the same time, the base shaft (0Cr17Ni4Cu4Nb) is also in a state of volume expansion. At this time, the residual stress of the H-DLC film is small and close to a stress-free state. After the preparation is completed, the shaft body (including the H-DLC film) is cooled to room temperature. Due to the mismatch between the thermal expansion coefficients of the shaft substrate and the H-DLC, the H-DLC film generates high residual stress. Excessive stress values will cause the bonding between the H-DLC film and the base shaft to deteriorate, and the H-DLC is prone to brittle fracture when impacted.
[0042] In order to reduce the residual stress of the H-DLC film on the surface of a rotating shaft, the present invention provides a rotating shaft and a method for manufacturing the rotating shaft.
[0043] like Figure 1-3 As shown, a rotating shaft includes a base shaft 1, the surface of the base shaft 1 is covered with a hard film 2, the hardness of the hard film 2 is greater than the hardness of the base shaft 1, and only a copper film 3 is arranged between the base shaft 1 and the hard film 2, and the hardness of the copper film 3 is less than the hardness of the base shaft 1.
[0044] A copper film 3 is arranged between the base shaft 1 and the hard film 2. Since the hardness of copper is lower than that of the base shaft 1 and the hard film 2, the copper film 3 can alleviate the high residual internal stress generated by the hard film 2 when the high temperature environment of the preparation is cooled to room temperature due to the mismatch of thermal expansion coefficients. The shaft using the copper film 3 as the intermediate transition layer has good film-base bonding and wear resistance. Figure 1-3 The shaft structure having the copper film 3 and the hard film 2 is shown.
[0045] Copper can reduce the interfacial residual stress for two main reasons: (i) interfacial relaxation at the interface between copper and DLC. Interfacial relaxation allows the original interfacial residual stress to cause the material to undergo plastic deformation and convert it into heat, thereby reducing the residual stress; (ii) copper does not form carbides with DLC, and copper atoms and carbon atoms are only connected by weak van der Waals forces.
[0046] Low residual stress requires that the thermal expansion coefficients of the materials are close and the lattice constants are similar. The lattice constant of copper is 0.36151nm, and the lattice constant of diamond is 0.357nm. The lattice constants of the two are similar. During preparation and deposition, there will be no high residual stress caused by the mismatch of atomic interface sizes due to the large difference in lattice constants.
[0047] Preferably, the hard film 2 is a H-DLC film.
[0048] H-DLC is the abbreviation of H-Diamond-like carbon, which refers to hydrogenated diamond-like carbon.
[0049] Hydrogenated diamond-like carbon (H-DLC) has high hardness and good wear resistance. The hard film 2 as the base shaft 1 can improve the wear resistance of the base shaft 1, so that the base shaft 1 can rotate stably.
[0050] In addition, the copper film 3 will not transform the SP3 hybrid bonds of the hard film 2 into SP2 hybrid bonds, while the SP2 hybrid bonds will reduce the bonding force between the hard film 2 and the base shaft 1 .
[0051] It can also prevent the problem of the film-base bonding strength being deteriorated due to the iron element in the iron-based alloy shaft catalyzing the Sp3 hybrid bonds of the hard film 2 to become Sp2 hybrid graphite.
[0052] Preferably, Figure 3 As shown, the thickness of the copper film 3 is H1, then 0.003mm≤H1≤0.004mm.
[0053] When the copper film 3 is too thin, such as less than 0.003mm, the copper film 3 is not enough to reduce the residual stress of H-DLC. When the copper film 3 is too thick, such as greater than 0.004mm, the copper film 3 itself has a low hardness and cannot provide sufficient support for H-DLC. When H-DLC is impacted, it is easy to deform and fracture. After testing, the copper film 3 with a thickness between 0.003mm and 0.004mm has the best effect.
[0054] Preferably, Figure 3 As shown, the thickness of the hard film 2 is H2, then 0.003mm≤H2≤0.004mm.
[0055] If the thickness of the hard film 2 is too small, such as less than 0.003mm, it is difficult to manufacture and has insufficient wear resistance, which makes it difficult to meet the use requirements. If the thickness of the hard film 2 is too large, such as greater than 0.004mm, the residual stress is too large, and the thinner copper film 3 cannot reduce its residual stress, and the thicker copper film 3 is difficult to provide sufficient support for the hard film 2. After testing, the best effect is achieved when the thickness of the hard film 2 is between 0.003mm and 0.004mm.
[0056] The residual stress of the H-DLC film without copper film 3 and the residual stress of the H-DLC film with copper film 3 (intermediate transition layer) were compared by simulation. The real temperature and mechanical environment of H-DLC film and H-DLC+copper film prepared by magnetron sputtering were simulated by finite element simulation, and the stress distribution of single-layer H-DLC film and single-layer H-DLC film+copper film 3 at room temperature was calculated.
[0057] Specifically, Figure 7 When there is no copper film 3, the axial stress distribution cloud diagram of the outer surface of the H-DLC film prepared at 500°C and then cooled to room temperature (about 20°C). Figure 4 The axial stress distribution cloud diagram of the outer surface of the H-DLC film prepared at 500°C and then cooled to room temperature (about 20°C) when the copper film 3 is provided; Figure 4 and Figure 7 It can be seen that the outer surface stress of H-DLC is basically the same. Figure 8 Schematic diagram of stress on the interface between H-DLC and base axis when there is no copper film; Figure 5 is a schematic diagram of stress on the bonding surface between H-DLC and the copper film 3 when the copper film 3 is present; Figure 8 It can be clearly seen that when there is no copper film, the axial stress of the H-DLC film is negative except at the edge, that is, the H-DLC film is in a compressive stress state, while the surface of the shaft substrate near the bonding surface is in a tensile stress state. Figure 5 and Figure 8 By comparison, it can be seen that the stress at the contact surface between H-DLC and the copper film 2 is smaller than the stress at the contact surface between H-DLC and the base shaft.
[0058] When there is no copper film 3, Fig. 9 As shown in Figure 2, the maximum value of the residual compressive stress (negative value) of the H-DLC film on the bonding surface is -2973.4Mpa; when there is a copper film 3, as shown in Figure 2 Figure 6 As shown, the maximum value of the residual compressive stress (negative value) of the H-DLC film at the bonding surface is -2645.5Mpa, so the H-DLC film provided with a copper film 3 (intermediate transition layer) can effectively reduce the residual stress by about 11%. Lower residual stress can effectively enhance the film-base bonding force and avoid brittle fracture. When the copper film 3 is provided, the reason why the residual stress of H-DLC is smaller is: first, the Young's modulus of copper is smaller and it is easy to produce greater strain; second, there are a large number of interfaces parallel to the surface of the substrate in the multilayer film. In the soft and hard alternating film system, the middle soft layer (copper film 3 in this application) plays the role of a shear band, thereby effectively reducing the internal stress and interface stress of the film layer; third, in the preparation of the H-DLC film, the diamond grains will be anchored on the deep copper matrix, which also increases the film-base bonding force to a certain extent.
[0059] The base shaft 1 is preferably an iron base shaft 1, and the base shaft 1 can be a hollow shaft. The outer diameter φ1 of the base shaft 1 is between 132 mm and 38 mm, and the inner diameter φ2 of the base shaft 1 is between 26 mm and 32 mm.
[0060] The present invention provides an air cycle machine, comprising an air dynamic pressure bearing 4 and the rotating shaft, wherein the top foil of the air dynamic pressure bearing 4 is opposite to the outer peripheral surface of the rotating shaft.
[0061] The present invention provides a method for manufacturing a rotating shaft, and the manufacturing method is used for manufacturing the above-mentioned rotating shaft;
[0062] The manufacturing method comprises: step 1, processing the surface of the base shaft; step 2, manufacturing a copper film on the surface of the base shaft; and step 3, manufacturing a hard film on the surface of the copper film.
[0063] Preferably, the base shaft 1 is an iron-based shaft 1, and the step 1 comprises:
[0064] S11: Grind the surface roughness of the base shaft 1 to not more than Ra0.08;
[0065] S12: The surface of the base shaft 1 is cleaned for 9 to 11 minutes, then ultrasonically cleaned for 14 to 16 minutes, and finally blown dry.
[0066] S11: The surface roughness of the base shaft 1 is polished to not more than Ra0.08; so that the copper film 3 formed by later sputtering can be tightly bonded to the base shaft 1; if the surface roughness of the base shaft 1 is too large, the surface roughness of the prepared copper film 2 is too large; if the surface roughness of the base shaft 1 is too low, the surface bonding area of the copper film 2 and the base shaft 1 becomes smaller, and the bonding force is poor.
[0067] S12: The surface of the base shaft 1 is cleaned for 9 to 11 minutes, then ultrasonically cleaned for 14 to 16 minutes, and finally blown dry to remove surface impurities; the cleanliness of the surface of the base shaft 1 is improved to facilitate subsequent work.
[0068] Preferably, the step 2 comprises:
[0069] S21: Place the copper target on the top of the magnetron sputtering chamber and evacuate the magnetron sputtering chamber to a pressure no greater than 5×10 - 5 Pa; evacuate the magnetron sputtering chamber to reduce the oxidizing gas and other gases in the magnetron sputtering chamber that are not conducive to the sputtering of the copper film 2.
[0070] S22: applying a voltage of -348V to -352V to the copper target, while sputtering the copper target with argon gas at a flow rate of not less than 30sccm, while maintaining the pressure in the magnetron sputtering chamber at 0.4Pa to 0.5Pa, the process lasts for 2.5 to 3.5 minutes; removing impurities and oxide film on the surface of the copper target. Preferably, the copper content of the copper target is above 99.9%. sccm is cubic centimeters per minute.
[0071] S23: Stop applying voltage to the copper target, place the base shaft 1 on the top of the magnetron sputtering chamber, and evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, and argon gas continues to sputter the copper target at a flow rate of not less than 30 sccm, while the pressure in the magnetron sputtering chamber is maintained at no more than 0.5 Pa, and the temperature in the sputtering chamber is between 50°C and 80°C. The process lasts for 45 to 55 minutes to form a copper film with a thickness of between 3μm and 4μm.
[0072] Preferably, S12 includes: cleaning the surface of the base shaft 1 with acetone, ultrasonically cleaning with anhydrous ethanol, and drying with nitrogen.
[0073] Preferably, the hard film is an H-DLC film, and the step three comprises:
[0074] S31: Replace the copper target with a graphite target with a purity of not less than 99.9% and place it on the top of the magnetron sputtering chamber. Evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, temperature is in the range of 480℃~520℃;
[0075] S32: A substrate bias voltage of -348V to -352V is applied to the graphite target, and at the same time, a mixed gas of argon and methane is sputtered on the graphite target at a flow rate of not less than 150sccm, wherein the ratio of argon to methane is between 2.2 and 2.3. The process lasts for 20 to 25 hours to form an H-DLC film with a thickness of between 3μm and 4μm.
[0076] Preferably, the step three further comprises:
[0077] S33: The temperature in the sputtering chamber is lowered to between 25°C and 30°C at a rate of (0.3-0.4)°C / min. The temperature is lowered slowly to avoid the stress of the base shaft 1, the copper film 2 and the H-DLC itself being unable to be effectively released due to the excessively fast cooling rate.
[0078] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.
Claims
1. A rotating shaft, comprising a base shaft (1), the surface of the base shaft (1) being covered with a hard film (2), the hardness of the hard film (2) being greater than the hardness of the base shaft (1), characterized in that: Only a copper film (3) is arranged between the base shaft (1) and the hard film (2), and the hardness of the copper film (3) is lower than the hardness of the base shaft (1).
2. The rotating shaft according to claim 1, characterized in that: The hard film (2) is hydrogenated diamond-like carbon.
3. The rotating shaft according to claim 1, characterized in that: The thickness of the copper film (3) is H1, then 0.003mm≤H1≤0.004mm.
4. The rotating shaft according to any one of claims 1 to 3, characterized in that: The thickness of the hard film (2) is H2, then 0.003mm≤H2≤0.004mm.
5. An air cycle machine, characterized in that: It comprises an air dynamic pressure bearing (4) and a rotating shaft according to any one of claims 1 to 4, wherein a top foil of the air dynamic pressure bearing (4) is opposite to an outer peripheral surface of the rotating shaft.
6. A method for manufacturing a rotating shaft, characterized in that: The manufacturing method is used for manufacturing the rotating shaft according to any one of claims 1 to 4; The manufacturing method comprises: step 1, processing the surface of a base shaft (1); step 2, manufacturing a copper film on the surface of the base shaft (1); and step 3, manufacturing a hard film on the surface of the copper film.
7. The method for manufacturing a rotating shaft according to claim 6, characterized in that: The base shaft (1) is an iron-based shaft (1), and the step 1 comprises: S11: grinding the surface roughness of the base shaft (1) to not more than Ra0.08; S12: The surface of the base shaft (1) is cleaned for 9 to 11 minutes, then ultrasonically cleaned for 14 to 16 minutes, and finally blown dry.
8. The method for manufacturing a rotating shaft according to claim 6, characterized in that: The step 2 comprises: S21: Place the copper target on the top of the magnetron sputtering chamber and evacuate the magnetron sputtering chamber to a pressure no greater than 5×10 -5 Pa; S22: applying a voltage of -348 V to -352 V to the copper target, while sputtering the copper target with argon gas at a flow rate of not less than 30 sccm, while maintaining the pressure in the magnetron sputtering chamber at 0.4 Pa to 0.5 Pa, and the process lasts for 2.5 to 3.5 minutes; S23: Stop applying voltage to the copper target, place the base shaft (1) on the top of the magnetron sputtering chamber, and evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, and argon gas continues to sputter the copper target at a flow rate of not less than 30 sccm, while the pressure in the magnetron sputtering chamber is maintained at not higher than 0.5 Pa, and the temperature in the sputtering chamber is between 50°C and 80°C. The process lasts for 45 to 55 minutes.
9. The method for manufacturing a rotating shaft according to claim 7, characterized in that: S12 includes: cleaning the surface of the base shaft (1) with acetone, ultrasonic cleaning with anhydrous ethanol, and drying with nitrogen.
10. The method for manufacturing a rotating shaft according to claim 6, characterized in that: The hard film is an H-DLC film, and the step three comprises: S31: Replace the copper target with a graphite target with a purity of not less than 99.9% and place it on the top of the magnetron sputtering chamber. Evacuate the magnetron sputtering chamber to a pressure of no more than 5×10 -5 Pa, temperature is in the range of 480℃~520℃; S32: applying a substrate bias voltage of -348V to -352V to the graphite target, and simultaneously sputtering the graphite target with a mixed gas of argon and methane at a flow rate of not less than 150sccm, wherein the ratio of argon to methane is between 2.2 and 2.5, and the process lasts for 20 to 25 hours.
11. The method for manufacturing a rotating shaft according to claim 10, characterized in that: The step three also includes: S33: Cooling the temperature in the sputtering chamber to between 25°C and 30°C at a rate of (0.3-0.4)°C / min.
Citation Information
Patent Citations
Ultra-hard carbon film and preparation method thereof
CN101554790A
Surface coating method of transmission mechanism
CN101671814A
Notebook computer rotating shaft protective sleeve
CN110687964A
CN composite film with DLC films with different hardness as buffer layers and preparation method of CN composite film
CN117684172A
Tubular body of fiber-reinforced resin and method for manufacturing the tubular body
JP2003127257A